INCIDENCE AND IDENTIFICATION OF BACTERIA IN SPOTS OF EXPOSITION AND COMMERCIALIZATION OF FRUITS AND VEGETABLES: A CASE STUDY - Fabiano, M. Z.; Forato, L. A.; Assis, O. B. G.; Bernardes-Filho, R. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The contamination of fruits and vegetables, due to pathogen activity, causes significant losses during postharvest and commercialization stage. Not solely an inadequate sanitization carried out on exposition and sales points, but also the lack of good practices and handling along the chain, favors the development of rots from microbial origin and secondary contamination along storage and commercialization conditions. Thus, the main aim of this study was to generate basic information useful for a better sanitization by using antimicrobial agents with efficiency in controlling the predominant microorganisms as identified in such sales spots. A case study was conducted by analyzing samples collected in an important commercial wholesale and retail market, specialized in the commercialization of fruits and vegetables, located in São Carlos, SP (Brazil), in which 46 types of bacteria were possible to be isolated and growth after sampling in several spots of exposition and commercialization. The grocery shelves and the scales were the points of higher microbial incidence. Most of the microorganisms were classified as gram-positive, though from 16 species identified as Gram-negative, 13 of them presented medium to high motility, being considered as organisms of elevate photogene potential. By means of genetic materials replication technique PCR (polymerase chain reaction), two dominant Gram-negative genera were identified: the Escherichia sp and Enterobacter sp., in different strains.